GAMBARAN AKSEPTOR KB TIDAK MENGGUNAKAN MKJP (METODE KONTRASEPSI JANGKA PANJANG) DI DESA DAWAN KALER KABUPATEN KLUNGKUNG TAHUN 2023 - Sutasning, Ni Wayan; Marhaeni, Gusti Ayu; Ayu Novya Dewi, I Gusti Agung (ARCHIVE OF COMMUNITY HEALTH, 2023)
ABSTRACT The still high population increase is an important problem faced by Indonesia in the Population Sector. The family planning program intends to control the population. Long- Term Contraception (MKJP) is a long-acting contraceptive drug used to prevent pregnancy, delay pregnancy, and overcome infertility. The purpose of the study was to determine the factors that I influence in the low coverage of the use of long-term contraceptive methodsI (MKJP). The data used is primary data, the type of research used is descriptive. The study was conducted in all mothers using non- MKJP family planning in Dawan Kaler Village, Klungkung. The study sample was 77 people using simple random sampling. The results of the study were the age factor of the majority aged 36 – 45 years (33.77%), the work factor was not working (48.52%), the education factor was mostly high school (41.56%), the largest knowledge factor was sufficient (44.16%), the attitude factor was mostly positive (75.32%) and the majority of husband support factors were not supportive (68.83%). The conclusion of this study was that most respondents were aged 36-45 years, did not work, had a high school education, sufficient level of knowledge, were positive and their husbands were not supportive. Keywords: Overview of KB Acceptors Not Using MKJP